2021
DOI: 10.1039/d0fo02917c
|View full text |Cite|
|
Sign up to set email alerts
|

Tracking physical breakdown of rice- and wheat-based foods with varying structures during gastric digestion and its influence on gastric emptying in a growing pig model

Abstract: There is currently a limited understanding of the effect of food structure on physical breakdown and gastric emptying of solid starch-based foods during gastric digestion. Moisture uptake, pH, particle size,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
70
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(84 citation statements)
references
References 80 publications
11
70
3
Order By: Relevance
“…These larvae may have hindered mixing of gastric juices with feed in the proximal stomach. This was also found in previous studies comparing rigid (e.g., roasted almonds) to soft (e.g., cooked rice) feed items ( 70 , 71 ). The consequences of a higher proximal stomach digesta pH for nutrient utilization are unclear, as this depends on numerous other factors such as gastric emptying rate and buffering capacity ( 70 , 71 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These larvae may have hindered mixing of gastric juices with feed in the proximal stomach. This was also found in previous studies comparing rigid (e.g., roasted almonds) to soft (e.g., cooked rice) feed items ( 70 , 71 ). The consequences of a higher proximal stomach digesta pH for nutrient utilization are unclear, as this depends on numerous other factors such as gastric emptying rate and buffering capacity ( 70 , 71 ).…”
Section: Discussionsupporting
confidence: 84%
“…This was also found in previous studies comparing rigid (e.g., roasted almonds) to soft (e.g., cooked rice) feed items (70,71). The consequences of a higher proximal stomach digesta pH for nutrient utilization are unclear, as this depends on numerous other factors such as gastric emptying rate and buffering capacity (70,71). The caecum of LL piglets was longer and marginally heavier than that of CC piglets.…”
Section: Post-weaningsupporting
confidence: 70%
“…These larvae may have hindered mixing of gastric juices with feed in the proximal stomach. This was also found in previous studies comparing rigid (e.g., roasted almonds) to soft (e.g., cooked rice) feed items (Bornhorst et al, 2014;Nadia et al, 2021). The consequences of a higher proximal stomach digesta pH for nutrient utilization are unclear, as this depends on numerous other factors such as gastric emptying rate and buffering capacity (Bornhorst et al, 2014;Nadia et al, 2021).…”
Section: Post-weaningsupporting
confidence: 66%
“…However, recently, it has been demonstrated that gastric starch digestion plays an important role in pigs [ 20 ]. Pigs demonstrated the ability to model human meal starch digestion [ 21 , 22 ].…”
Section: Mouth and Stomachmentioning
confidence: 99%
“…Coarse feed increased mean retention time and improved the fractioning of gastric content [ 16 ]. Larger particle size resulted in higher pH at the proximal part of the stomach than at the distal part [ 21 ]. This also can be manifested in altered microbiota (members of the genera Lactobacillus and Mitsuokella and propionate and butyrate producers are stimulated) [ 27 ].…”
Section: Mouth and Stomachmentioning
confidence: 99%